Bike to work socialization program as environmentally friendly behavior to the community to prevent global warming - Puspita, Hapsari Shinta Cinta; Erta, Erta; Supriyanto, Catur (Technium Sustainability, 2022)
There has been a lot of talk lately about a green culture, because of the scale of the consequences of global warming. One of the facts that we experience as a result of global warming is the increasing temperature of our environment. Global warming is the impact of human activities that are more related to business than environmental protection. Global warming is not only warming, but also has a bad impact that anyone can see and feel. When the earth’s temperature continues to increase, it will have adverse effects that are interrelated with one another. Global warming will affect the earth’s conditions in an extreme way. To anticipate the worsening global warming, the local government cooperates with the University in Surabaya in an effort to carry out socialization related to efforts to prevent global warming. Many efforts have been made by the State University of Surabaya as a form of preventing global warming. Among the efforts that have been made by UNESA in reducing global warming, including UNESA doing greening in the campus environment this is done as a form of reducing global warming. The urgency of this community service is motivated by the problem of global warming which has not been resolved until now. Through the UNESA LPPM program in this community service scheme. This PKM research team seeks to provide socialization to the community, especially UNESA students to move to protect the surrounding environment, in order to reduce global warming. In addition, the output targets in this Community Service include: Articles of publications, publications of mass media, products.